Preparation method of high-wear-resistance air valve plate ceramic material

By using materials such as alumina, zirconia, rare earth oxides, and combined with the modification process of carboxymethyl cellulose and fatty acid modified nanocellulose, a highly wear-resistant gas valve sheet ceramic material was prepared, which solved the problem of poor softening and corrosion resistance of existing materials at high temperatures and achieved excellent performance of ceramic materials under high temperatures and high pressures.

CN119751026AActive Publication Date: 2025-04-04HUNAN KUANGCHU TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411920342.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing gas valve sheet materials are prone to softening and deforming at high temperatures, and have poor corrosion resistance, making it difficult to meet the wear resistance requirements of engine valves under high temperature, high pressure and mechanical load.

Method used

A ceramic material composed of aluminum oxide, zirconia, rare earth oxide, carboxymethyl cellulose and fatty acid modified nanocellulose was prepared by ball milling and spray granulation processes, and then sintered under an inert gas atmosphere.

Benefits of technology

The prepared ceramic materials have excellent mechanical properties, good pressure, heat, corrosion and wear resistance, and can maintain stability at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751026A_ABST
    Figure CN119751026A_ABST
Patent Text Reader

Abstract

The invention relates to the field of wear-resistant ceramic materials, in particular to a preparation method of a high-wear-resistant air valve plate ceramic material, which comprises the following steps: ball-milling ceramic powder to obtain slurry, adding a binder consisting of carboxymethyl cellulose and fatty acid modified nano cellulose and a sulfate surfactant into the slurry, continuously ball-milling, and spray-granulating to obtain composite powder; the composite powder is pressed into a blank, finally, the blank is sintered in the inert gas atmosphere, and the ceramic material prepared through the method has excellent mechanical performance and good pressure resistance, heat resistance, corrosion resistance and abrasion resistance, and it can be known through comparison that the ceramic material has good application prospects. The addition of zirconium oxide, samarium oxide, ytterbium oxide, carboxymethyl cellulose, fatty acid modified nano cellulose and lauryl sodium sulfate plays a positive role in improving various properties of the ceramic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wear-resistant ceramic materials, in particular to a method for preparing a highly wear-resistant valve plate ceramic material. Background Art

[0002] As an important part of the engine valve mechanism, the valve is not only a part of the combustion chamber, but also a channel for fresh air and high-temperature exhaust gas to enter and exit the combustion chamber. The intake valve controls the introduction of fresh air into the cylinder, and the exhaust valve discharges the exhaust gas after combustion. Good valve quality is the guarantee for the engine to provide good power performance, environmental performance, and economic performance.

[0003] During operation, the valve needs to withstand high temperature, high pressure, and mechanical and thermal loads of hundreds or even thousands of times per minute, and will be subjected to constantly changing tension, pressure, impact, friction, and thermal stress. In order to meet the harsh working conditions of the exhaust valve, the material used to manufacture the valve plate must have good wear resistance, corrosion resistance, and high temperature resistance. Currently, alloy materials are mostly used as the raw materials for making valve plates. Although they have the advantages of good thermal conductivity and relatively low price, they are easy to soften and deform at high temperatures and have poor corrosion resistance. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for preparing a highly wear-resistant valve plate ceramic material.

[0005] The technical solutions adopted are as follows:

[0006] A method for preparing a highly wear-resistant valve plate ceramic material:

[0007] The ceramic powder is ball-milled to obtain a slurry, a binder composed of carboxymethyl cellulose and fatty acid-modified nanocellulose and a sulfate surfactant are added to the slurry, the ball-milling is continued and then spray-granulated to obtain a composite powder, the composite powder is pressed into a green body, and finally the green body is sintered in an inert gas atmosphere.

[0008] Furthermore, the ceramic powder includes aluminum oxide, zirconium oxide and rare earth oxide.

[0009] Furthermore, the weight ratio of the aluminum oxide, zirconium oxide and rare earth oxide is 80-100:10-20:1-3.

[0010] Furthermore, the rare earth oxide is composed of samarium oxide and ytterbium oxide in a weight ratio of 1-5:1-5.

[0011] Furthermore, the amount of the binder is 5-10% of the weight of the ceramic powder.

[0012] Furthermore, the weight ratio of the carboxymethyl cellulose to the fatty acid modified nanocellulose is 1-5:1-5.

[0013] Furthermore, the preparation method of the fatty acid-modified nanocellulose is as follows:

[0014] Dissolve the nanocellulose in LiCl / DMAc solution, then add fatty acid, 4-toluenesulfonyl chloride and pyridine, and react the resulting mixture at 70-90°C for 18-36 hours. Pour the reaction solution into water / methanol solution, filter out the precipitated solid, extract with methanol solution for 18-36 hours and then dry.

[0015] Furthermore, the fatty acid is any one or more combinations of lauric acid, myristic acid and palmitic acid.

[0016] Furthermore, during sintering, the temperature is first raised to 800-850°C and kept for 1-3 hours, then raised to 1100-1200°C and kept for 1-3 hours, then raised to 1450-1550°C and kept for 1-3 hours, then lowered to 800-1000°C, and finally cooled to room temperature in the furnace.

[0017] Furthermore, the first stage heating rate is 10-20°C / min, the second stage heating rate is 1-5°C / min, the first stage heating rate is 1-5°C / min, and the cooling rate is 1-5°C / min.

[0018] Beneficial effects of the present invention:

[0019] The invention provides a preparation method of a highly wear-resistant valve plate ceramic material. Carboxymethyl cellulose forms a firm network structure in a slurry by hydrogen bonding and van der Waals force, thereby exhibiting bonding performance. Nanocellulose modified with fatty acid can play a dispersing role together with sulfate surfactants during ball milling, and form a stable emulsion with carboxymethyl cellulose and sulfate surfactants, so that composite powder with uniform texture is formed after spray granulation, laying a foundation for compression molding. The nanocellulose can also be used as a carbon source to generate different types of carbides inside a ceramic material matrix through a carbon thermal reduction reaction, thereby improving various properties of the ceramic material. Zirconium oxide and rare earth oxide can optimize the microstructure of the ceramic material, refine ceramic grains, and improve mechanical and wear resistance, and can also be used as raw materials for carbon thermal reduction reaction. The ceramic material prepared by the invention has relatively excellent mechanical properties, and good pressure resistance, heat resistance, corrosion resistance and wear resistance. By comparison, it can be seen that the addition of zirconium oxide, samarium oxide, ytterbium oxide, carboxymethyl cellulose, fatty acid-modified nanocellulose and sodium dodecyl sulfate all play a positive role in improving various properties of the ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1It is a schematic diagram of a testing device for wear resistance in the performance test of the present invention. DETAILED DESCRIPTION

[0021] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0022] Embodiment 1:

[0023] A method for preparing a highly wear-resistant valve plate ceramic material:

[0024] 180g of alumina, 35g of zirconium oxide, 2g of samarium oxide and 1g of ytterbium oxide were mixed evenly, and the mixed powder was put into a grinding tank at a ratio of material: ball = 1:2, and dry-milled at 180r / min for 30min, and then deionized water of the same weight as the powder was added to continue wet-milling for 12h to obtain a slurry, and 7.5g of carboxymethyl cellulose, 7.5g of fatty acid-modified nanocellulose and 10g of sodium dodecyl sulfate were added to the slurry, and the ball milling was continued for 30min before spray granulation. The air inlet temperature was set to 180℃, the air outlet temperature to 100℃, and the peristaltic pump speed to 60r / min, the atomizer speed is 6000r / min, the composite powder obtained after spray granulation is collected, and after aging for 24h, it is pressed into a billet under a cold isostatic pressing pressure of 100MPa, and the billet is placed in an argon-protected muffle furnace, first heated to 850℃ at a speed of 15℃ / min, and sintered for 1.5h, then heated to 1150℃ at a speed of 5℃ / min, and sintered for 1h, then heated to 1550℃ at a speed of 2℃ / min, and sintered for 2h, then cooled to 850℃ at a speed of 1℃ / min, and finally cooled to room temperature with the furnace.

[0025] Wherein, the preparation method of fatty acid modified nanocellulose is as follows:

[0026] Take 20g of nanocellulose (degree of polymerization 1000) and dissolve it in 500ml of 9wt% LiCl / DMAc solution. Then add 0.15g of lauric acid, 0.14g of 4-toluenesulfonyl chloride and 0.12g of pyridine. The resulting mixture is reacted at 80°C for 24h. The reaction solution is poured into 5L of water / methanol solution (water and methanol volume ratio 1:1), the precipitated solid is filtered out, extracted with methanol solution for 24h and then dried.

[0027] Embodiment 2:

[0028] A method for preparing a highly wear-resistant valve plate ceramic material:

[0029] 200g of alumina, 40g of zirconium oxide, 1g of samarium oxide and 1g of ytterbium oxide were mixed evenly, and the mixed powder was put into a grinding tank at a ratio of material: ball = 1:2, and dry-milled at 180r / min for 30min, and then deionized water of the same weight as the powder was added to continue wet-milling for 12h to obtain a slurry, and 7.5g of carboxymethyl cellulose, 7.5g of fatty acid-modified nanocellulose and 10g of sodium dodecyl sulfate were added to the slurry, and the ball milling was continued for 30min before spray granulation. The air inlet temperature was set to 180℃, the air outlet temperature to 100℃, and the peristaltic pump speed to 60r / min, the atomizer speed is 6000r / min, the composite powder obtained after spray granulation is collected, and after aging for 24h, it is pressed into a billet under a cold isostatic pressing pressure of 100MPa, and the billet is placed in an argon-protected muffle furnace, first heated to 850℃ at a rate of 20℃ / min and sintered for 1h, then heated to 1200℃ at a rate of 5℃ / min and sintered for 1h, then heated to 1550℃ at a rate of 2℃ / min and sintered for 2h, then cooled to 1000℃ at a rate of 2℃ / min, and finally cooled to room temperature with the furnace.

[0030] The preparation method of fatty acid-modified nanocellulose is the same as that in Example 1.

[0031] Embodiment 3:

[0032] A method for preparing a highly wear-resistant valve plate ceramic material:

[0033] 160g of alumina, 20g of zirconium oxide, 3g of samarium oxide and 3g of ytterbium oxide were mixed evenly, and the mixed powder was put into a grinding tank at a ratio of material: ball = 1:2, and dry-milled at 180r / min for 30min, and then deionized water of the same weight as the powder was added to continue wet-milling for 12h to obtain a slurry, and 7.5g of carboxymethyl cellulose, 7.5g of fatty acid-modified nanocellulose and 10g of sodium dodecyl sulfate were added to the slurry, and the ball milling was continued for 30min before spray granulation. The air inlet temperature was set to 180℃, the air outlet temperature to 100℃, and the peristaltic pump speed to 60r / min, the atomizer speed is 6000r / min, the composite powder obtained after spray granulation is collected, and after aging for 24h, it is pressed into a billet under a cold isostatic pressing pressure of 100MPa, and the billet is placed in an argon-protected muffle furnace, first heated to 800℃ at a rate of 10℃ / min, and sintered for 2h, then heated to 1100℃ at a rate of 5℃ / min, and sintered for 1h, then heated to 1450℃ at a rate of 1℃ / min, and sintered for 2h, then cooled to 800℃ at a rate of 1℃ / min, and finally cooled to room temperature with the furnace.

[0034] The preparation method of fatty acid-modified nanocellulose is the same as that in Example 1.

[0035] Comparative Example 1:

[0036] It is basically the same as Example 1, except that zirconium oxide is not added.

[0037] Comparative Example 2:

[0038] Basically the same as Example 1, except that samarium oxide is not added.

[0039] Comparative Example 3:

[0040] It is basically the same as Example 1, except that ytterbium oxide is not added.

[0041] Comparative Example 4:

[0042] The method is substantially the same as Example 1, except that carboxymethyl cellulose is not added.

[0043] Comparative Example 5:

[0044] Basically the same as Example 1, except that no fatty acid-modified nanocellulose is added.

[0045] Comparative Example 6:

[0046] It is basically the same as Example 1, except that the nanocellulose is directly added without being modified by fatty acid.

[0047] Comparative Example 7:

[0048] The method is substantially the same as Example 1, except that sodium lauryl sulfate is not added.

[0049] Performance testing:

[0050] The ceramic materials prepared in Examples 1-3 and Comparative Examples 1-7 of the present invention were used as samples for performance testing;

[0051] ① The three-point bending method is used to test the bending strength of the sample. The test method refers to GB / T 6569-2006 "Fine Ceramics Bending Strength Test Method", and the loading speed is 1mm / min;

[0052] ② The fracture toughness of the sample was tested by the single-sided pre-cracked beam method. The test method referred to GB / T23806-2009 "Fine Ceramics Fracture Toughness Test Method Single-sided Pre-cracked Beam (SEPB) Method".

[0053] ③Reference Figure 1A testing device was used, and the sample was fixed on the sample table with a pressing plate. Si3N4 ceramic balls with a diameter of 5 mm were selected as the grinding material. The lifting bracket and the balance weight were adjusted to make the beam horizontally balanced. The experimental parameters were set as follows: Friction type: dry friction at room temperature, load size: 3N, rotation speed: 150r / min, friction circle radius: 2mm, test time: 1800s; a white light interferometer three-dimensional profilometer was used to scan the wear scar surface to obtain the cross-sectional morphology of the wear scar, and the position-depth curves of 4 positions were selected and integrated through the origin mapping software to obtain the cross-sectional area of ​​the wear scar and calculate the average value. The wear scar volume was calculated through the ring volume formula, which is the wear volume.

[0054] The formula for the volume of the ring is: V = 2πRS

[0055] (R is the distance from the centroid of the cross section to the center of the ring, and S is the cross-sectional area)

[0056] The performance test results are shown in Table 1 below:

[0057] Table 1:

[0058]

[0059] It can be seen from Table 1 above that the ceramic material prepared by the present invention has relatively excellent mechanical properties and good wear resistance;

[0060] By comparison, it can be seen that the addition of zirconium oxide, samarium oxide, ytterbium oxide, carboxymethyl cellulose, fatty acid-modified nanocellulose and sodium dodecyl sulfate has played a positive role in improving the performance of ceramic materials.

[0061] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a highly wear-resistant valve plate ceramic material, characterized in that: The ceramic powder is ball-milled to obtain a slurry, a binder composed of carboxymethyl cellulose and fatty acid-modified nanocellulose and a sulfate surfactant are added to the slurry, the ball-milling is continued and then spray-granulated to obtain a composite powder, the composite powder is pressed into a green body, and finally the green body is sintered in an inert gas atmosphere.

2. The method for preparing the highly wear-resistant valve plate ceramic material according to claim 1, characterized in that: The ceramic powder comprises aluminum oxide, zirconium oxide and rare earth oxide.

3. The method for preparing the highly wear-resistant valve plate ceramic material according to claim 2, characterized in that: The weight ratio of the aluminum oxide, zirconium oxide and rare earth oxide is 80-100:10-20:1-3.

4. The method for preparing the highly wear-resistant valve plate ceramic material according to claim 3, characterized in that: The rare earth oxide is composed of samarium oxide and ytterbium oxide in a weight ratio of 1-5:1-5.

5. The method for preparing the highly wear-resistant valve plate ceramic material according to claim 1, characterized in that: The amount of the binder is 5-10% of the weight of the ceramic powder.

6. The method for preparing the highly wear-resistant valve plate ceramic material according to claim 1, characterized in that: The weight ratio of the carboxymethyl cellulose to the fatty acid modified nanocellulose is 1-5:1-5.

7. The method for preparing a highly wear-resistant valve plate ceramic material according to claim 1, characterized in that: The preparation method of the fatty acid modified nanocellulose is as follows: Dissolve the nanocellulose in LiCl / DMAc solution, then add fatty acid, 4-toluenesulfonyl chloride and pyridine, and react the resulting mixture at 70-90°C for 18-36 hours. Pour the reaction solution into water / methanol solution, filter out the precipitated solid, extract with methanol solution for 18-36 hours and then dry.

8. The method for preparing the highly wear-resistant valve plate ceramic material according to claim 7, characterized in that: The fatty acid is any one or more combinations of lauric acid, myristic acid and palmitic acid.

9. The method for preparing a highly wear-resistant valve plate ceramic material according to claim 1, characterized in that: During sintering, the temperature is first raised to 800-850℃ and kept for 1-3h, then raised to 1100-1200℃ and kept for 1-3h, then raised to 1450-1550℃ and kept for 1-3h, then lowered to 800-1000℃, and finally cooled to room temperature with the furnace.

10. The method for preparing a highly wear-resistant valve plate ceramic material according to claim 9, characterized in that: The heating rate of the first stage is 10-20℃ / min, the heating rate of the second stage is 1-5℃ / min, the heating rate of the first stage is 1-5℃ / min, and the cooling rate is 1-5℃ / min.

Citation Information

Patent Citations

  • Preparation method of high-wear-resistance water seal ceramic wafer

    CN118344129A

  • Alumina-fiber-reinforced ceramic material and method of manufacturing said material

    EP0538492A1

  • High-strength zirconia-alumina composite ceramic substrate applied to semiconductor device and manufacturing method thereof

    US20220017422A1

  • KR20240100306A